Cocoa Jargon in Latin America and the Caribbean - Bharah, Sarah (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2025)
The glossary provides simple and functional explanations for specific words and acronyms used in the literature of the project. The list is not exhaustive, but a collation of terms that may carry somewhat different meanings throughout the Latin America and Caribbean region.